Analisis Penerapan SAK Koperasi Pasca Pencabutan PSAK 27 tentang Penyajian Laporan Keuangan Koperasi Pegawai Republik Indonesia (KPRI) UPI Bandung - Ade Pipit Fatmawati; Jaka Maulana (Badan Penerbit Fakultas Ekonomi dan Bisnis Universitas Singaperbangsa Karawang, 2022)
Revocation of cooperative standards namely PSAK 27 on cooperative accounting by the Indonesian Institute of Accountants has had a major impact on the preparation of cooperative financial statements. The purpose of this study is to find answers regarding how the application of Cooperative Financial Accounting Standards Post PSAK Revocation 27 Concerning Presentation of Cooperative Financial Statements.The standard was replaced by Regulation of the Minister of Cooperatives and Small and Medium Enterprises Number 12 / Per / M.KUKM / IX / 2015 Concerning the General Guidelines for Cooperative Accounting for the Real Sector. In this research, the method used is a qualitative approach with a case study model.. Data collection is done by means of interview techniques and documentation techniques From the research results it is known that in general KPRI still applies PSAK No.27 in the presentation of its financial statements even though in some cases there have been changes in the presentation patterns. This can be seen from the presentation of cooperative financial statements From the data obtained it is known that the cooperative has made at least three of the five elements of a complete financial statement from the cooperative, namely: Balance Sheet, Calculation of Operating Results, and Cash Flow report. Where the cooperative should also make a notes of the financial statement and equity statement.